Lithium / sodium / zinc metal negative electrode based on polymer solid electrolyte interface layer modification and preparation method of lithium / sodium / zinc metal negative electrode

The covalent frame structure material (COF) formed by the covalent frame structure material (COF) of the lithium/sodium/zinc metal negative surface coating oxygen oxylene graphene modification solves the problem of the solid lithium battery interface, significantly increased the cycle life of the battery and the Curren Efficiency ensure battery safety and efficient operation.

CN119361839APending Publication Date: 2025-01-24JIANGHAN UNIVERSITY +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411449436.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The capacity of existing solid-state lithium batteries is not high and the circulation and rate performance is low, mainly due to the interface problems between the electrolyte and the positive and negative electrodes, including the space charge layer, interface reaction and interface contact loss.

Method used

Using a method based on polymer solid electrolyte interface layer modification, the electrode/electrolyte interface is improved by uniformly drop-coating a polymer interface layer with a regular pore structure and rich lithiophilic sites on the surface of the lithium/sodium/zinc metal anode. The interface layer is composed of a graphene oxide-modified covalent organic framework material (COF). The composite COF@GO material is prepared by a hydrothermal method to form a highly stable artificial solid-state electrolyte interface layer.

Benefits of technology

It significantly improves the cycle life and Kuron efficiency of lithium batteries, suppress the formation of lithium branches, ensure the safety of batteries, and can operate stably at high current density. The capacity retention rate of the battery reaches 83%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361839A_ABST
    Figure CN119361839A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium / sodium / zinc metal negative electrode based on polymer solid electrolyte interface layer modification and a preparation method thereof.The method comprises the steps that a COF material is synthesized with GO as a substrate, namely, a COF-coated GO material is synthesized, the COF-coated GO and a DME solution are mixed and then dropwise coated on the surface of lithium metal, a layer of artificial SEI film is constructed on the surface of the lithium metal, and the surface of the lithium metal is coated with the COF-coated GO by means of the structural rule of the COF-coated GO and the rich lithium-loving framework; by adjusting uniform transportation of lithium ions, anchoring electrolyte anions and promoting desolvation, the cycle life of a half battery and the cycle stability of a symmetrical battery are improved, and the specific discharge capacity of the ternary positive electrode material with high energy density is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery interface material design, and specifically relates to a lithium / sodium / zinc metal negative electrode modified based on a polymer solid electrolyte interface layer and a preparation method thereof. Background Art

[0002] With the development of electric vehicles and portable electronic devices, the demand for high energy density rechargeable batteries has increased significantly. Lithium metal has a low redox potential (-3.04V vs. SHE) and a high theoretical capacity (3860mAhg -1 ), has received widespread attention; interface stability is one of the important factors affecting the electrochemical performance of solid-state lithium batteries. Although the lithium ion conductivity of solid electrolytes has reached the level of liquid electrolytes in recent years, the battery capacity is still not high, and the cycle and rate performance are much lower than traditional organic electrolyte batteries. After in-depth research, it was found that the key factors that determine battery capacity and high-rate performance are not only the ionic conductivity of solid electrolytes and the electrochemical window of electrolytes, but also the interface problems between electrolytes and positive and negative electrodes. Common interface problems mainly include space charge layer, interface reaction, and interface contact loss.

[0003] The space charge layer refers to the migration of lithium ions from the solid electrolyte to the oxide positive electrode side when the positive electrode material and the solid electrolyte come into contact. The reason is that the positive electrode active material of the lithium battery is usually a mixture of high ionic conductivity and electronic conductivity, while the solid electrolyte is a single ion conductor, and there is a large chemical potential difference between the lithium ions.

[0004] The lack of interfacial contact refers to the lack of contact between the solid electrolyte and the positive electrode material particles due to the repeated volume changes of most positive electrode materials during the charge and discharge process. The lack of interfacial contact will also cause an increase in interfacial impedance and a loss of battery capacity.

[0005] Interfacial reaction refers to the reaction between the lithium metal anode and the electrolyte interface in solid-state batteries, forming a mixed conductive phase interface with high ionic and electronic conductivity. The mixed conductive interface layer will continue to react with lithium metal, consuming electrolyte and lithium anode materials. The mixed conductive phase interface may help stabilize the interface in the early stage, but in the long run, this conductive path may lead to more electron loss and irreversible reaction, and eventually lead to battery failure.

[0006] In addition to the interfacial reaction between the solid electrolyte and the lithium anode, when the current density and surface capacity are too large, lithium metal will preferentially nucleate and grow inside the solid electrolyte and at the grain boundaries, and may develop into lithium dendrites, which can penetrate the electrolyte, causing internal short circuits and eventual failure.

[0007] Therefore, it is necessary to develop a simple method to prepare a highly stable solid electrolyte interface layer.

[0008] Interface protection is one of the important strategies to stabilize metallic lithium. It can be roughly divided into two types. One is to construct a natural SEI with better stability by designing the electrolyte system; the other is to construct an artificial SEI with specific components. Compared with the former method, artificial SEI has better controllability and is convenient for large-scale application. Improving the mechanical strength and ionic conductivity of organic polymer SEI is critical to its commercialization. Organic matter has good flexibility, but low mechanical strength, difficulty in suppressing dendrites, and low ionic conductivity. Therefore, improving the mechanical strength and ionic conductivity of organic polymer SEI is critical to its commercialization. Summary of the invention

[0009] Based on the above problems, the present invention provides a highly stable artificial solid electrolyte interface layer modified lithium negative electrode material and its preparation method and application. The present invention aims at the problem that the lithium metal negative electrode has high chemical reaction activity but poor electrolyte stability, resulting in short battery cycle life, low coulombic efficiency, and safety problems caused by lithium dendrite growth during the cycle. The present invention provides a simple in-situ grown polymer layer containing a COF structure, its preparation method and application in lithium batteries, so that fast ion transport can be achieved at the electrode / electrolyte interface.

[0010] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0011] A method for preparing a lithium / sodium / zinc metal negative electrode based on a polymer solid electrolyte interface layer modification comprises the following steps:

[0012] The solid electrolyte interface layer is evenly drop-coated on the surface of the lithium / sodium / zinc metal negative electrode in a vacuum or inert gas environment. After being fully allowed to stand and dry, a lithium / sodium / zinc metal negative electrode modified with a polymer solid electrolyte interface layer is obtained.

[0013] The solid electrolyte interface layer has a regular pore structure and abundant lithium-philic sites.

[0014] The preparation of the polymer solid electrolyte interface layer comprises the following steps:

[0015] Step 1, selecting an organic linker and an amine monomer to synthesize an ion conductor covalent organic framework material, i.e., a precursor COF;

[0016] Step 2, uniformly dispersing the precursor COF obtained in step 1 into a graphene oxide (GO) solution, and preparing a composite COF@GO material by a hydrothermal method;

[0017] Step 3: Take 0.1-0.5 mg of COF@GO material in step 2 and dissolve it in DME solution. After sufficient stirring, a precursor mixture, i.e., a solid electrolyte interface layer, is obtained.

[0018] Preferably, the thickness of the lithium / sodium / zinc metal negative electrode is 15 mm, and the thickness of the solid electrolyte interface layer is about 2 um.

[0019] Preferably, the specific steps of step 1 are: injecting degassed N-methyl-2-pyrrolidone solvent into the organic linker and the amine monomer, dissolving them in an oil bath, slowly adding H2SO4, heating them in the oil bath, quenching the reaction when cooling, and obtaining a brown precipitate; then performing separation, washing, extraction, and drying to finally obtain a precursor COF material;

[0020] The organic linker in step 1 is cyclohexanehexol,

[0021] The amine monomers include 1,2,4,5-tetraaminobenzene, 1,3,5-tris(4-aminophenyl)benzene, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 2,4,6-tris(4-aminophenyl)-pyridine, 2,4,6-tris(4-aminophenyl)-pyrimidine, tris(4-aminophenyl)-amine, 1,3,5-tris(4'-amino[1,1'-biphenyl]-4- One of 1,3,5-tris(4'-amino[1,1'-biphenyl]-4-yl)-benzene, 1,3,5-tris(4'-amino[1,1'-biphenyl]-4-yl)-1,3,5-triazine, 1,3,5-tris(4'-amino[1,1'-biphenyl]-4-yl)-pyridine, 1,3,5-tris(4'-amino[1,1'-biphenyl]-4-yl)-pyrimidine, and 1,3,5-tris(4'-amino[1,1'-biphenyl]-4-yl)-amine;

[0022] The molar ratio of the alcohol group in the cyclohexanehexol in the organic linker to the amino group in the amine monomer is 1:1.

[0023] The specific steps of step 2 include dispersing 48 mg of the precursor COF prepared in step 2 into 1000 ml of deionized water solution configured with 0.2 mg / ml graphene oxide (GO).

[0024] The present invention also protects the application of the lithium metal negative electrode prepared by the method in the field of lithium / sodium / zinc ion batteries.

[0025] Preferably, one of the application methods is:

[0026] Preparation of positive electrode sheets: pressing and cutting lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium manganese oxide;

[0027] Preparation of electrolyte: dissolving LiTFSI, LiFSI or LiPF6 in an organic solvent to prepare a LiTFSI, LiFSI or LiPF6 electrolyte with a concentration of 1 mol / L;

[0028] Wherein, the organic solvent is composed of two or more of carbonate solvents or organic ether solvents;

[0029] The carbonate solvent is selected from ethyl carbonate, diethyl carbonate, propylene carbonate or fluoroethylene carbonate; the organic ether solvent is selected from ethylene glycol dimethyl ether, 1,3-dioxolane, 1,2-dimethoxypropane, tetrahydrofuran or 2-methyltetrahydrofuran;

[0030] Preparation of lithium-ion batteries: The positive electrode, separator, electrolyte and negative electrode of metal lithium secondary battery are assembled in sequence to make a lithium-ion battery.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The present invention modifies the ion conductor covalent organic framework material by graphene oxide, thereby constructing a simple in-situ grown polymer layer containing a Li-N structure, namely, an ASEI layer. When the interface layer is coated on the surface of the lithium metal negative electrode, the ionic conductivity of the assembled battery is greater. This is because, on the one hand, graphene oxide itself has a π-π conjugated aromatic hydrocarbon structure, which can form a Li-π structure and greatly shorten the transportation path of lithium ions. On the other hand, the COF material itself has a porous structure and a lithium-philic skeleton. When the interface layer is modified by GO, the contact angle between the interface layer and the electrolyte is smaller, and the interface wettability of the solid electrolyte interface layer is better. That is to say, the lithium-philic skeleton and regular through-hole structure of GO and COF itself play a synergistic role. When the material is coated, the lithium ion flux can be redistributed, the side reaction between lithium metal and electrolyte can be reduced, and the uniform transportation of lithium ions is provided to ensure the safety of the battery.

[0033] 2. The lithium metal negative electrode protected by this interface layer effectively inhibits the side reaction decomposition of the electrode and the electrolyte, uniforms the lithium deposition, avoids the formation of lithium dendrites, and greatly improves the cycle life and coulombic efficiency of the battery. -2 , 1mAh·cm -2 Under the condition of 1.5 mol·s, the symmetrical battery composed of lithium negative electrode materials modified by the artificial solid electrolyte interface layer can stably cycle for more than 3500 h with an overpotential below 5 mV. The Li-COF@GO|NCM811 battery paired with 24 mg of NCM811 active material has a capacity retention rate of about 83% after 100 cycles at a rate of 0.5C; this work provides a new solution for the practical application of lithium metal negative electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic diagram of the preparation process of the lithium negative electrode material interface layer modified by in-situ chemical construction of an artificial solid electrolyte interface layer;

[0035] Figure 2 The lithium negative electrode material modified by the artificial solid electrolyte interface layer of Example 1, the symmetrical battery assembled by Comparative Example 1 and Comparative Example 2 is 1 mA cm -2 , 1mAhcm -2 Comparison of voltage-time curves under ;

[0036] Figure 3 It is a comparison of the coulombic efficiency of the lithium negative electrode material modified by the artificial solid electrolyte interface layer of Example 1, the Li|Cu half-cell assembled by Comparative Example 1 and Comparative Example 2;

[0037] Figure 4 It is a comparison of the full battery impedance diagrams of the lithium negative electrode material modified by the artificial solid electrolyte interface layer of Example 1, Comparative Example 1 and Comparative Example 2;

[0038] Figure 5 It is a comparison chart of the long cycle performance of the lithium negative electrode material modified by the artificial solid electrolyte interface layer of Example 1, Comparative Example 1 and the full battery of Comparative Example 2 at a rate of 0.5C. DETAILED DESCRIPTION

[0039] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0040] The polyolefin separator used in the following examples is from Asahi KASEI Co., Ltd., and the thickness of the polyolefin separator is 9-20 μm.

[0041] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:

[0042] Example 1

[0043] A method for preparing a lithium negative electrode material modified by an artificial solid electrolyte interface layer comprises the following steps:

[0044] (1) 312 mg of cyclohexanehexol and 426 mg of 1,2,4,5-tetraaminobenzene were mixed in a 50 mL flask, 50 mL of degassed N-methyl-2-pyrrolidone (NMP) solvent was added, and the mixture was dissolved in an oil bath at 100°C.

[0045] (2) After cooling to room temperature, replace the ice bath and heat it to room temperature. Slowly add 1 ml of H2SO4 to avoid oxidation of the reagent. After 1 hour, heat in an oil bath at 160°C for 12 hours. When cooling, quench the reaction with 250 mL of ethanol and observe a brown precipitate.

[0046] (3) The brown precipitate obtained in step (2) was washed three times with ethanol, NaHCO3 aqueous solution and deionized water alternately at 9000 rad min -1 Centrifuge, then perform Soxhlet extraction in ethanol for 7 days. Dry the extracted material in a vacuum oven at 60°C for 5 days to obtain the final precursor COF product.

[0047] (4) Disperse 48 mg of the precursor COF product prepared in step (3) into 1000 ml of deionized water solution containing 2 mg / ml graphene oxide (GO), and obtain a composite COF@GO material by hydrothermal reaction.

[0048] (5) In a glove box filled with argon (<0.1ppm H2O and O2), the lithium sheet is polished to remove surface impurities to obtain a pretreated metal lithium foil, which is fresh and bright; 0.1-0.5mg COF@GO material is dissolved in 1-5ml 1,2-dimethoxyethane (DME) solution, mixed thoroughly, and stirred at room temperature for 24h to obtain a precursor mixture, which is then drop-coated on the pretreated metal lithium foil with a thickness of 2um. After drying, a lithium negative electrode material modified with an artificial solid electrolyte interface layer is obtained. The modified lithium sheet is referred to as Li-COF@GO here.

[0049] As shown in Table 1, we also tested the ionic conductivity of the synthesized COF@GO powder material. It can be clearly observed that the ionic conductivity of the COF material modified with GO (0.92) is higher than that of Comparative Example 1 (3.7) and Comparative Example 2 (1.4). This is attributed to the π-π conjugated structure of graphene oxide itself, which realizes Li + -π combination can shorten the lithium ion transport pathway. The contact angle of the modified lithium sheet Li-COF@GO obtained in Example 1 is 17°, which is smaller than the contact angles of Comparative Example 1 (37°) and Comparative Example 2 (46°), proving that the porous structure and lithium-philic skeleton of COF@GO lead to the artificially constructed solid electrolyte interface layer, which can improve the interface wettability.

[0050] Afterwards, the lithium negative electrode material modified by the artificial solid electrolyte interface layer, namely Li-COF@GO, was combined with different battery electrodes and assembled into half-cells, symmetrical cells and full cells for electrochemical performance testing.

[0051] Comparative Example 1

[0052] Referring to the preparation method of Example 1, a lithium negative electrode material modified by an artificial solid electrolyte interface layer that has not been modified by graphene oxide comprises the following steps:

[0053] (1) 312 mg of cyclohexanehexol and 426 mg of 1,2,4,5-tetraaminobenzene were mixed in a 50 mL flask, 50 mL of degassed N-methyl-2-pyrrolidone (NMP) solvent was added, and the mixture was dissolved in an oil bath at 100°C.

[0054] (2) After cooling to room temperature, replace the ice bath and heat it to room temperature. Slowly add 1 ml of H2SO4 to avoid oxidation of the reagent. After 1 hour, heat in an oil bath at 160°C for 12 hours. When cooling, quench the reaction with 250 mL of ethanol and observe a brown precipitate.

[0055] (3) The brown precipitate obtained in step (2) was washed three times with ethanol, NaHCO3 aqueous solution and deionized water alternately at 9000 rad min -1 Centrifuge, then perform Soxhlet extraction in ethanol for 7 days. Dry the extracted material in a vacuum oven at 60°C for 5 days to obtain the final precursor COF product.

[0056] (4) In a glove box filled with argon (<0.1ppm H2O and O2), the lithium sheet is polished to remove surface impurities to obtain a pretreated metal lithium foil, which is fresh and bright; 0.1mg COF material is dissolved in 1ml 1,2-dimethoxyethane (DME) solution, mixed thoroughly, and stirred at room temperature for 24h to obtain a precursor mixture, which is then drop-coated on the pretreated metal lithium foil with a thickness of 7um. After drying, a lithium negative electrode material coated with an artificial solid electrolyte interface layer is obtained.

[0057] The lithium negative electrode material coated with the artificial solid electrolyte interface layer was then combined with different battery electrodes and assembled into half-cells, symmetrical cells and full cells for electrochemical performance testing.

[0058] Comparative Example 2

[0059] Referring to the preparation method of Example 1, a lithium negative electrode material modified by an artificial solid electrolyte interface layer is prepared. The difference from Example 1 is that the preparation monomer of the covalent organic framework structure COF is different. The specific steps are as follows:

[0060] (1) At room temperature, 282 mg of 1,3,5-tris(4-aminophenyl)benzene (TAPB) and 160 mg of terephthalaldehyde (PDA) were mixed in a 50 mL flask, injected with 50 mL of degassed N-methyl-2-pyrrolidone (NMP) solvent, and dissolved in an oil bath at 100 °C to prepare a thin COF film layer via an in situ Schiff base reaction.

[0061] (2) After cooling to room temperature, replace the ice bath and heat it to room temperature. Slowly add 1 ml of H2SO4 to avoid oxidation of the reagent. After 1 hour, heat in an oil bath at 160°C for 12 hours. When cooling, quench the reaction with 250 mL of ethanol and observe a yellow precipitate.

[0062] (3) The crude yellow precipitate obtained in step (2) was washed three times with ethanol, NaHCO3 aqueous solution and deionized water alternately at 9000 rad min -1 Centrifuge, then perform Soxhlet extraction in ethanol for 7 days. Dry the extracted material in a vacuum oven at 60°C for 5 days to obtain the final precursor COF product.

[0063] (4) The lithium sheet is polished in a glove box filled with argon (<0.1ppm H2O and O2) to remove surface impurities, thereby obtaining a pretreated metal lithium foil, which is fresh and bright; then the precursor COF product is drop-coated on the pretreated metal lithium foil with a thickness of 10um, and after drying, a lithium negative electrode material modified by an artificial solid electrolyte interface layer is obtained.

[0064] The physical and chemical properties of the monomers in Comparative Example 2 are unstable, the reaction is difficult to control, and side reactions are likely to occur, resulting in a reduction in the yield of the target product. Compared with Comparative Example 1, it is not easy to control the amount of monomers to synthesize the precursor COF, while the monomers in Comparative Example 1 have stable chemical properties, are relatively cheap, are easier to obtain, and have carbon chain lengths that are easier to control. They have functional groups, and by adjusting the ratio of carbon chain lengths and alcohol groups, GO can be better loaded and can better participate in the Schiff base reaction to obtain the target product.

[0065] The lithium negative electrode material modified by the artificial solid electrolyte interface layer was then combined with different battery electrodes and assembled into half-cells, symmetrical cells and full cells for electrochemical performance testing.

[0066] Example 2

[0067] Symmetrical batteries composed of the lithium negative electrode materials modified with the interface layers obtained in Example 1, Comparative Example 1 and Comparative Example 2 were prepared, and electrochemical performance tests were performed.

[0068] 1. Preparation of electrolyte: Dissolve 1.0 mol / L lithium bis(trifluoromethane)imide (LiTFSI) in 1,3-dioxane (DOL) and 1,2-dimethoxyethane (DME) (V / V=1:1), mix well and set aside.

[0069] 2. Assemble button cells (CR2032): Use the modified lithium metal sheet as the positive electrode, the mixed solution obtained in step 1 as the electrolyte and the separator, and the modified lithium metal sheet as the negative electrode to assemble a symmetrical button cell (CR2032) in a glove box filled with argon. -2 , 1mAhcm -2 Constant current charge and discharge test was performed under

[0070] In the control group, both the positive and negative electrodes were replaced with polished lithium metal foil, and the other preparation steps were the same to obtain a Li|Li symmetric battery.

[0071] like Figure 2 The results show that at 1mAcm -2 , 1mAhcm -2 Under the charge and discharge test, the electrochemical performance of the Li@COF|Li@COF symmetric battery of Example 1 is the best, and it can stably cycle for more than 3500 hours. Its polarization voltage is low, far below 5mv, which indicates that the ASEI of Li-COF@GO can more effectively inhibit dendrite growth when working at high current density.

[0072] The symmetrical cells in Comparative Examples 1 and 2 were -2 , 1mAhcm -2 In the charge and discharge test, when comparative example 1 is used as the artificial solid electrolyte interface layer modified lithium negative electrode material, the cycle stability time is 400h, and the polarization voltage of the modified symmetrical battery is large. At the same time, comparative example 2 has an obvious short circuit after a long period of cycling, indicating that the COF material without GO modification has poor cycle stability.

[0073] On the other hand, as shown in Table 1, the ionic conductivity of the lithium negative electrode materials modified by the artificial solid electrolyte interface layer synthesized in Example 1, Comparative Example 1 and Comparative Example 2 was tested. It can be clearly observed that the ionic conductivity (9.2) of the COF material modified by graphene oxide (GO) in Example 1 is significantly higher than that of Comparative Example 1 (3.7) and Comparative Example 2 (1.4). The contact angle of the modified lithium sheet Li-COF@GO obtained in Example 1 is 17°, which is smaller than the contact angles of Comparative Example 1 (37°) and Comparative Example 2 (46°), proving that the porous structure and lithium-philic skeleton of COF@GO enable the artificially constructed solid electrolyte interface layer to improve the interface wettability.

[0074] In Comparative Examples 1 and 2, GO was not used for modification in the prepared COF materials. Although the COF material was coated on the surface of the lithium foil to redistribute the lithium ion flux, reduce the side reaction between lithium metal and the electrolyte, and inhibit the formation of dendrites on the lithium negative electrode to ensure battery safety, the COF material modified with GO in Example 1 had a cycle stability time of more than 3500 hours under the same test conditions, and the polarization voltage was much lower than 5mv. This is due to the modification of the COF material by graphene oxide (GO). Since graphene oxide itself has a π-π conjugated aromatic hydrocarbon structure, it can form a Li-π structure, which can greatly shorten the transport pathway of lithium ions. In combination with the lithium-philic skeleton and regular through-hole structure of COF itself, the side reaction between lithium metal and the electrolyte can be reduced after the material is coated, providing favorable assistance for the uniform transport of lithium ions.

[0075] Table 1 Comparison of the physicochemical properties of the interface layers of different lithium anode materials

[0076]

[0077] Example 3

[0078] A lithium copper battery composed of the lithium negative electrode material modified by the interface layer obtained in Example 1 was prepared, and the electrochemical performance was tested.

[0079] 1. Preparation of electrolyte: Dissolve 1.0 mol / L lithium bis(trifluoromethane)imide (LiTFSI) in 1,3-dioxane (DOL) and 1,2-dimethoxyethane (DME) (V / V=1:1), mix well and set aside;

[0080] 2. Assemble button cells (CR2032): Assemble the positive electrode (metallic copper), separator, electrolyte, and the modified lithium sheet Li@COF obtained in Example 1 as the negative electrode in sequence, and assemble the button cells (CR2032) in a glove box filled with argon.

[0081] In the control group, the negative electrode was replaced with polished lithium metal foil, and the other preparation steps were the same to obtain a Li|Cu half-cell.

[0082] Figure 3 The results show that at 1mAcm -2 , 1mAhcm -2 Under the charge and discharge test, the electrochemical performance of the Li-COF@GO|Cu half-cell is optimal, and it can stably cycle for more than 280 cycles, with an average coulombic efficiency of 98.7%. The cycle life of the half-cells of Comparative Example 1 and Comparative Example 2 is less than 100 cycles, which shows that Li-COF@GO can effectively reduce the consumption of lithium by the electrolyte, inhibit the growth of lithium dendrites, and increase the battery cycle life.

[0083] Example 4

[0084] In this example, Comparative Example 1, Comparative Example 2 and Li-COF@GO were used as negative electrodes, NCM811 was used as positive electrodes, 1MLiPF6 EC / DEC (volume ratio of 1:1) was used as electrolyte, and polypropylene diaphragms were used to assemble NCM811 batteries in an argon atmosphere glove box. The polypropylene diaphragm used in this step was from AsahiKASEI Company, and the thickness of the diaphragm was 9-20 μm.

[0085] The preparation method of the NCM811 positive electrode sheet is as follows: nickel cobalt manganese (NCM), SuperP (conductive carbon black), and polyvinylidene fluoride (PVDF) binder are mixed in a mass ratio of 8:1:1, ground evenly and dispersed in polymethylpyrrolidone (NMP), then placed in a homogenizer and homogenized for 20 minutes to obtain a uniform slurry, and the slurry is scraped onto aluminum foil with a preparation device and placed in a vacuum drying oven at 80°C for 12 hours.

[0086] The above assembled battery was subjected to electrochemical impedance spectroscopy (EIS) test to study the migration behavior of Li+ on ASEI. Figure 4 As shown, the charge transfer impedance Rct of the Li-COF@GO|NCM811 battery is much lower than that of Comparative Example 1 and Comparative Example 2, which means that the Li+ transport resistance through the interface membrane is reduced, and Li+ migrates faster through ASEI, achieving high-speed and uniform lithium ion flux transportation.

[0087] Example 6

[0088] In this example, lithium metal is used as the negative electrode, NCM811 is used as the positive electrode, 1M LiPF6 EC / DEC (volume ratio is 1:1) is used as the electrolyte, and a polypropylene separator is used, wherein the negative electrode metal lithium is respectively assembled into NCM811 batteries in an argon atmosphere glove box with Li and Li@COF. The polypropylene separator used in this step is from AsahiKASEI Company, and the thickness of the separator is 9-20μm.

[0089] The preparation method of the positive electrode sheet is as follows: nickel cobalt manganese (NCM), SuperP (conductive carbon black), and polyvinylidene fluoride (PVDF) binder are mixed in a mass ratio of 8:1:1, ground evenly and dispersed in polymethylpyrrolidone (NMP), and then placed in a homogenizer for 20 minutes to obtain a uniform slurry, and the slurry is scraped onto aluminum foil with a preparation device and placed in a vacuum drying oven at 80°C for 12 hours.

[0090] The long cycle performance of 2.8~4.3V was tested under the condition of 0.5C rate, 1C=200mAhg -1 , the amount of NCM811 active substance is 24mg, Figure 5 The cycling performance of Li-COF@GO, comparative example 1, and comparative example 2 at 0.5C rate.

[0091] like Figure 5 As shown in the figure, after the first three cycles of activation at 0.1C, Li-COF@GO has a first cycle of 194 mAhg -1 The discharge capacity of the first cycle is 185.36 mAh g -1 The discharge capacity of the battery is 195.58 mAh g after 100 cycles. -1 The discharge specific capacity of the battery is 27% after 100 cycles. At the same time, there is no COF-modified lithium metal that can be used with high-surface-load ternary materials for long-term cycle testing. After 100 cycles, the capacity retention rate can reach 83%. The COF modified with GO can achieve such a high capacity retention rate, which is attributed to the coordination of our artificially constructed SEI membrane and the CEI membrane formed by the NCM811 positive electrode material, which can allow lithium ions to be transported evenly and play a role in homogenizing the lithium flow.

[0092] Example 7

[0093] In order to further study the ion transport dynamics of the artificial solid electrolyte interface layer, Tafel experiments were carried out on the assembled Li-COF@GO, comparative example 1, and comparative example 2 symmetric cells (Table 1). The voltage test range was -0.2 to 0.2 V, and the scan rate was 1 mVs -1 The exchange current density of the Li@COF symmetric cell was calculated by Tafel curve to be 0.55 mA cm -2 , much higher than the comparative example 1 (0.11mAcm -2 ) and Comparative Example 2 (0.05 mA cm -2 ).

[0094] The COF material synthesized on the basis of graphene oxide (GO) has multiple lithium-philic skeletons. After GO modification, the rich π-π conjugated structure on the GO skeleton and the variable chemical environment of the π electron cloud provide guarantees for electrochemical energy storage and conversion. It can coordinate with lithium ions to form a Li-π structure, shorten the lithium ion transmission path, and make the lithium ion plating / stripping process more intense and rapid.

[0095] Example 8

[0096] The lithium ion migration number of the Li-COF@GO symmetric battery was determined by assembling the battery; the battery reached a steady state after 1500s at a polarization voltage of 10mV, and the initial and steady-state Nyquist plots were tested. As shown in Table 1, when COF@GO is used as an artificial solid electrolyte interface layer of the lithium metal anode, it has a high lithium ion migration number of up to 0.95, which is much higher than that of Comparative Example 1 (0.68) and Comparative Example 2 (0.54) without GO modified COF.

[0097] In this embodiment, the lithium ion migration number of the modified lithium sheet of COF modified by GO reaches 0.95, which is attributed to the rich π-π conjugated structure on the GO skeleton. The variable chemical environment of the π electron cloud provides a guarantee for electrochemical energy storage and conversion, and can coordinate with lithium ions to form a Li-π structure, which greatly shortens the lithium ion transmission path. Lithium ions can obtain a better migration path, thereby increasing the lithium ion migration number.

[0098] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a polymer solid electrolyte interface layer for lithium metal negative electrode modification, characterized in that The following steps are involved: Step 1, selecting an organic linker and an amine monomer to synthesize an ion conductor covalent organic framework material, i.e., a precursor COF; Step 2, uniformly dispersing the precursor COF obtained in step 1 into a graphene oxide (GO) solution, and preparing a composite COF@GO material by a hydrothermal method; Step 3: Take 0.1-0.5 mg of COF@GO material in step 2 and dissolve it in DME solution. After sufficient stirring, a precursor mixture, i.e., a solid electrolyte interface layer, is obtained.

2. A method for preparing a lithium / sodium / zinc metal negative electrode based on a polymer solid electrolyte interface layer modification, characterized in that: Here are the steps: The solid electrolyte interface layer obtained in claim 1 is evenly drop-coated on the surface of the lithium / sodium / zinc metal negative electrode in a vacuum or inert gas environment, and after being fully allowed to stand and dry, a lithium / sodium / zinc metal negative electrode modified with a polymer solid electrolyte interface layer is obtained.

3. The method for preparing the lithium / sodium / zinc metal negative electrode according to claim 2, characterized in that: The thickness of the lithium / sodium / zinc metal negative electrode is 15 mm, and the thickness of the solid electrolyte interface layer is about 2 um.

4. The method for preparing a lithium / sodium / zinc metal negative electrode according to claim 2, characterized in that: The specific steps of step 1 are: injecting the organic linker and the amine monomer into a degassed N-methyl-2-pyrrolidone solvent, dissolving them in an oil bath, slowly adding H2SO4, heating them in an oil bath, quenching the reaction when cooling, and obtaining a brown precipitate; Subsequently, separation, washing, extraction and drying are performed to finally obtain the precursor COF material; The organic linker in step 1 is cyclohexanehexol, The amine monomers include 1,2,4,5-tetraaminobenzene, 1,3,5-tris(4-aminophenyl)benzene, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 2,4,6-tris(4-aminophenyl)-pyridine, 2,4,6-tris(4-aminophenyl)-pyrimidine, tris(4-aminophenyl)-amine, 1,3,5-tris(4'-amino[1,1'-biphenyl]-4- One of 1,3,5-tris(4'-amino[1,1'-biphenyl]-4-yl)-benzene, 1,3,5-tris(4'-amino[1,1'-biphenyl]-4-yl)-1,3,5-triazine, 1,3,5-tris(4'-amino[1,1'-biphenyl]-4-yl)-pyridine, 1,3,5-tris(4'-amino[1,1'-biphenyl]-4-yl)-pyrimidine, and 1,3,5-tris(4'-amino[1,1'-biphenyl]-4-yl)-amine; The molar ratio of the alcohol group in the cyclohexanehexol in the organic linker to the amino group in the amine monomer is 1:

1.

5. The method for preparing a lithium / sodium / zinc metal negative electrode according to claim 2, characterized in that: The specific steps of step 2 include dispersing 48 mg of the precursor COF prepared in step 2 into 1000 ml of deionized water solution configured with 0.2 mg / ml graphene oxide (GO).

6. Application of the lithium metal negative electrode prepared by the method according to any one of claims 1 to 5 in the field of lithium / sodium / zinc ion batteries.

Citation Information

Cited By

  • Mixed ion conductor layer for lithium metal negative electrode, preparation method of mixed ion conductor layer and all-solid-state battery

    CN120978016A

  • A hybrid ionic conductor layer for a lithium metal negative electrode, a preparation method thereof, and a full solid-state battery

    CN120978016B